2015
DOI: 10.3390/su7066457
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-Related Food Waste: Causes and Potential for Action

Abstract: Abstract:In the past decade, food waste has received increased attention on both academic and societal levels. As a cause of negative economic, environmental and social effects, food waste is considered to be one of the sustainability issues that needs to be addressed. In developed countries, consumers are one of the biggest sources of food waste. To successfully reduce consumer-related food waste, it is necessary to have a clear understanding of the factors influencing food waste-related consumer perceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
549
2
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 681 publications
(579 citation statements)
references
References 59 publications
14
549
2
14
Order By: Relevance
“…Beyond these basic factors, several studies and surveys have found that consumers' culinary skills and, more generally, information and awareness on the wider implications of food (e.g., nutritional properties and related dietary effects, conditions of safe use, cultural aspects, social and environmental implications) have a positive correlation with a reduced generation of FW in the households, since they contribute to create a positive attitude towards good practices at different levels: planning of food shopping and meals at home, food storage, meal preparation and portioning, reuse of leftovers and optimisation of food available at home, donation of the food that cannot be consumed for any reason, and sorting of kitchen waste [13][14][15]17,22,25,104,134,147,153,154,158,[175][176][177].…”
Section: Fw Drivers Related To Consumers' Individual Behaviours Modifmentioning
confidence: 99%
“…Beyond these basic factors, several studies and surveys have found that consumers' culinary skills and, more generally, information and awareness on the wider implications of food (e.g., nutritional properties and related dietary effects, conditions of safe use, cultural aspects, social and environmental implications) have a positive correlation with a reduced generation of FW in the households, since they contribute to create a positive attitude towards good practices at different levels: planning of food shopping and meals at home, food storage, meal preparation and portioning, reuse of leftovers and optimisation of food available at home, donation of the food that cannot be consumed for any reason, and sorting of kitchen waste [13][14][15]17,22,25,104,134,147,153,154,158,[175][176][177].…”
Section: Fw Drivers Related To Consumers' Individual Behaviours Modifmentioning
confidence: 99%
“…Health issues are considered to be part of the numerous trends which have recently appeared on the food market [24] and seem to have a personal and social value [25]. Nowadays, consumers are more informed about the food they are eating and they have become more aware of the link between food and health [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A wide variety of psychological factors, such as attitude, perceived behavior control, and subjective norms, have been identified as influential in household waste recycling behavior. Furthermore, in recent years, there has been increasing awareness towards household KW, especially towards how to reduce household KW at the source in developed countries [35][36][37][38][39][40]. However, few researchers have considered the KW separately in developing countries, or the difference between recyclable (e.g., paper, aluminum, plastic, glass, cardboard, and batteries) and KW, and all have treated the entire waste as a whole in their studies.…”
Section: Introductionmentioning
confidence: 99%